LncRNA MALAT1 Promotes PPARα/CD36-Mediated Hepatic Lipogenesis in Nonalcoholic Fatty Liver Disease by Modulating miR-206/ARNT Axis - Xiang, Juan; Deng, Yuan-Yuan; Liu, Hui-Xia; Pu, Ying (Frontiers in Bioengineering and Biotechnology, 2022)
CD36 is the target protein of NAFLD01, which is an aptamer we selected from NAFLD cell by Cell-SELEX. Long non-coding RNAs (lncRNAs) are known to play crucial roles in nonalcoholic fatty liver disease (NAFLD). This research sought to explore mechanisms by which lncRNA MALAT1 regulates the progression of NAFLD. Thus, in order to detect the function of MALAT1 in NAFLD, in vitro and in vivo model of NAFLD were established. Then, fatty acid uptake and triglyceride level were investigated by BODIPY labeled-fatty acid uptake assay and Oil red O staining, respectively. The expressions of MALAT1, miR-206, ARNT, PPARα and CD36 were detected by western blotting and qPCR. Dual luciferase, RIP and ChIP assay were used to validate the relation among MALAT1, miR-206, ARNT and PPARα. The data revealed expression of MALAT1 was up-regulated in vitro and in vivo in NAFLD, and knockdown of MALAT1 suppressed FFA-induced lipid accumulation in hepatocytes. Meanwhile, MALAT1 upregulated the expression of ARNT through binding with miR-206. Moreover, miR-206 inhibitor reversed MALAT1 knockdown effects in decreased lipid accumulation in FFA-treated hepatocytes. Furthermore, ARNT could inhibit the expression of PPARα via binding with PPARα promoter. Knockdown of MALAT1 significantly upregulated the level of PPARα and downregulated the expression of CD36, while PPARα knockdown reversed these phenomena. MALAT1 regulated PPARα/CD36 -mediated hepatic lipid accumulation in NAFLD through regulation of miR-206/ARNT axis. Thus, MALAT1/miR-206/ARNT might be served as a therapeutic target against NAFLD.